Evaluation of the Brief Wisconsin Inventory of Smoking Dependence Motives in African-American and European-American Heavy Smokers - Ma, Jennie Z.; Li, Ming D.; Payne, Thomas J. (Frontiers in Psychiatry, 2012)
Introduction: Emerging evidence indicates that nicotine dependence should be measured multidimensionally. A brief version of the Wisconsin Inventory of Smoking Dependence Motives (WISDM) has recently been developed in which the item count has been reduced from 68 to 37. The objectives of this study were to replicate the initial findings in a larger heavy-smoking sample, and determine whether the WISDM structure is applicable to both African-American (AA) and European-American (EA) heavy smokers. Methods: Smokers were selected from our Mid-South Tobacco Family and Case-Control studies. Available data from 2,522 smokers was selected, involving 1,633 AA and 889 EA participants. Both exploratory and confirmatory analyses were employed to evaluate the psychometric characteristics of the Brief WISDM. Results: AAs and EAs were similar in age, sex, education, marital status, CPD, and FTND score. Internal consistency evaluations for Brief WISDM subscales were adequate but generally lower than that of the full-scale version. Confirmatory factor analyses did not yield desirable fits for AA or EA smokers. Exploratory factor analysis revealed good agreement for item loadings on the four Primary Dependence Motives subscales (Automaticity, Loss of Control, Craving, and Tolerance) but discrepancies on all Secondary Dependence Motives subscales except Taste/Sensory Processes. Specific item loadings for subscales differed by ethnicity. Conclusions: The Brief WISDM demonstrated reasonable psychometric properties in our large sample. Together, we provide support for the general validity of the brief form but suggest individual item selections may benefit from further investigation.